2018
DOI: 10.1080/19932820.2018.1433418
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous lidocaine as adjuvant to general anesthesia in renal surgery

Abstract: The role of intraoperative intravenous lidocaine infusion has been previously evaluated for pain relief, inflammatory response, and post-operative recovery, particularly in abdominal surgery. The present study is a randomized double-blinded trial in which we evaluated whether IV lidocaine infusion reduces isoflurane requirement, intraoperative remifentanil consumption and time to post-operative recovery in non-laparoscopic renal surgery. Sixty patients scheduled to undergo elective non-laparoscopic renal surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
5
5
0
2
Order By: Relevance
“…The present study indicated that the use of opioids in the lidocaine group was less than that in the control group, consistent with the results of a previous study (30). Intravenous lidocaine may inhibit the discharge of neurons and fibres by blocking sodium channels (31) and reduce the threshold of peripheral noxious stimulation to achieve analgesic and pain desensitization effects (32).…”
Section: Discussionsupporting
confidence: 92%
“…The present study indicated that the use of opioids in the lidocaine group was less than that in the control group, consistent with the results of a previous study (30). Intravenous lidocaine may inhibit the discharge of neurons and fibres by blocking sodium channels (31) and reduce the threshold of peripheral noxious stimulation to achieve analgesic and pain desensitization effects (32).…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies showed that a remifentanil sparing effect of intravenous lidocaine in the intraoperative period was found [18], which was consistent with our findings. However, another study reported that perioperative intravenous lidocaine infusion had no significant effect on remifentanil requirement during hypotensive anesthesia for elective transsphenoidal endoscopic hypophyseal adenoma excision procedure [19].…”
Section: Discussionsupporting
confidence: 93%
“…Administration of intravenous lidocaine was shown to have an opioid sparing effect during GA, including fentanyl [16], sufentanil [17] and morphine [18]. In a recent study, the remifentanil sparing effect of intravenous lidocaine in the intraoperative period was found [19], which was consistent with our findings. However, another study reported that perioperative intravenous lidocaine infusion had no significant effect on remifentanil requirement during hypotensive anesthesia for elective transsphenoidal endoscopic hypophyseal adenoma excision procedure [20].…”
Section: Discussionsupporting
confidence: 91%